ΕΡΕΥΝΗΤΙΚΗ ΑΠΟΣΤΟΛΗ ΣΤΗ ΡΟΥΜΑΝΙΑ. ΕΛΛΗΝΙΚΕΣ ΚΟΙΝΟΤΗΤΕΣ (1829 - ΑΡΧΕΣ 20ΟΥ ΑΙΩΝΑ). ΚΑΤΑΣΤΑΤΙΚΑ - ΣΥΛΛΟΓΟΙ - ΤΑΥΤΟΤΗΤΕΣ. ΕΙΣΑΓΩΓΙΚΕΣ ΠΑΡΑΤΗΡΗΣΕΙΣ - ΚΟΝΤΟΓΕΩΡΓΗΣ ΔΗΜΗΤΡΙΟΣ Μ. (Eoa kai Esperia, 2007)
While there exists already a voluminous bibliography on the GreekDiaspora in the Danubian Principalities during the 17th-18th centuries, it wasonly recently that interest was focused on the Greek communities, whichflourished in Romania in the period from the signing of the Andrianople Treatyto the 20th century. It was during that era that a great number of Greeks, especially from Epirus,Cephallonia and Ithaca, merchants, sailors, artisans, doctors and intellectualsimmigrated to Wallachia and Moldavia. The majority of them established at theDanubian ports, mainly at Braila and Galatz, and were engaged in the vividcommerce between the principalities and Western Europe. Notwithstanding the influential role played by the Greeks in the social andeconomic life of Romania, it was only in the Cuza-Era when the Greekcommunities were officialy founded. Probably the nationalistic state policyurged them to define their legal status more explicitly. Moreover, in the secondhalf of the 19th century a great number of churches was built and many schoolswere organized, some subsided by the community authorities, other bybenefactory associations. Furthermore, the fierce antagonism among Greeks,Jews, Austrian and English shipowners did not impede the development of themarine and riverine fleet of the Greek shipowners, while a substantial numberof banks and factories were also owned by members of the communities. In the second part of this study are presented the results of our researchmission in various Romanian cities. The aim of our mission was to locatearchival fonds and collections referring to the economic, social, institutional andpolitical history of the Greek Diaspora in Romania. Important collections arebequeathed in the Archives of Bucharest, Galatz and Constantza, while in theArchives of Giurgiu, Tulcea and Craiova the material was less satisfactory.